Association of Fear of COVID-19 and Health Literacy Among the General Public in Saudi Arabia: A Cross-Sectional Assessment - Moussa, Mahaman L.; Moussa, Fatchima Laouali; Alharbi, Homood A.; Omer, Tagwa; Sofiany, Hussain Ahmad; Almuzaini, Tarraji Mohammed; Alsaady, Eissa Salem; Alrashede, Sattam Musleh (Frontiers in Public Health, 2022)
Objective This study aims to determine the level of fear of COVID-19 among the general public in Saudi Arabia and the association of its scores with their level of health literacy. Methods A descriptive cross-sectional study was conducted among the general population in Saudi Arabia from April 2020 to May 2020. A three-part online self-reported survey was used to assess participants’ demographic characteristics, fear of COVID-19 of the participants, and levels of health literacy. Results Of the 848 participants, 56.8% were in the age group of 25 – 34, 45.6% were females and 57.1% had a bachelor’s degree. The total mean score of the fear of COVID-19 scale of the participants was M= 19.60 SD 7.33 and the health literacy was M= 27.57 SD 11.07. There was a significant difference in scores of fear of COVID-19 scale in terms of age (F=2.442, p=0.050), representing aged 45 and above had higher mean fear score than those younger participants. The analysis revealed an increased level of fear of COVID-19 was associated with older age (B=1.87; p= 0.020), being unemployed (B=0.76; p= 0.023), with no formal education (B= 0.89; p= 0.001) and low level of health literacy (B= 0.02; p= 0.021). Conclusion The study shows an above-average level of fear of COVID-19 of the general public in Saudi Arabia and its association with a low level of functional health literacy. Timely and comprehensive health interventions should be promoted to enhance the level of health literacy and further reduce the level of fear of COVID-19 in the community.